Concussions in Collision Youth Sports - Kathleen A. Linzmeier; Cynthia R. LaBella (Pediatric Neurology Briefs Publishers, 2016)
Investigators from the University of Pittsburg, University of Arkansas, Lake Erie College of Osteopathic Medicine, and Boston Children's Hospital/Harvard Medical College researched the incidence of concussions in youth hockey in relation to age and activity setting.